Implementing Process Reading Strategy through Instagram Media to Improve the Students’ Ability in Reading Comprehension at 8th Grade of SMPN 2 Lubuk Pakam - Liswina Nainggolan; Kammer Sipayung; Nurhayati Sitorus; Hersakso Sinurat (Innovative: Journal Of Social Science Research, 2023)
This research aimed to find out the use of reading strategy through Instagram media in improving students’ reading comprehension. This research was conducted at SMPN 2 Lubuk Pakam. A Classroom Action Research was used as research design. The population of this research was students at VIII grade of the academic year 2022/2023 where the total of the entire population is 289 students. The sample of this research was students VIII2 grade which there are 31 students in total. By using critical reading and CIRC (Cooperative Integrated Reading Composition) strategy. The finding showed that the use of critical reading and CIRC (Cooperative Integrated Reading Composition) strategy which was assisted by Instagram media can improve the students’ reading comprehension. It based on the result of the students’ reading test in pre-test compared with the students’ reading test in cycle 1 and cycle 2. In pre-test, the students’ mean score is 59, post-test in cycle 1 the students’ mean score is 67.1, post-test in cycle 2 the students’ mean score is 73.8 where students' reading ability from pre-test to post-test improved 23.7% while the percentage students who pass KKM in post-test 2 is 74.19%. From the data gathered, it can be concluded that Critical reading and CIRC strategy assisted by Instagram media has a significant role to improve students’ reading comprehension